Chloroquine in the COVID-19 Pandemics and Quinine in the Cattle Plague Epidemics in the Eighteenth Century: Déjà Vu All Over Again - Franco, Giuliano (European Journal of Oncology and Environmental Health, 2023)
Drug treatment of diseases is not a usual task for occupational and environmental physicians. However, these professionals should be aware that some concerns on treatment during an epidemics were raised centuries ago.This commentary discusses Bernardino Ramazzini's remarks made during a cattle plague epidemics occurring four centuries before the current COVID-19 emergency; he emphasised that prescription of some drugs usually given against every kind of fever deserved careful attention.Ramazzini's contribution can be regarded as an early example of attention to evaluating the benefits and harmful effects of taking new drugs and witnesses the scientists' continuous effort to tackle new and unexpected health challenges.